Phytoremediation of heavy metals contaminated soil samples obtained from mechanic workshop and dumpsite using Amaranthus spinosus - Kelechi L. Njoku; Simeon O. Nwani (Scientific African, 2022)
This study investigated the potential of Amaranthus spinosus for the remediation of heavy metal contaminated soils a mechanic workshop and refuse dumpsites. The plant was grown in each soil for 12 weeks. The heavy metals were extracted from the samples using HNO3 digestion and analyzed using atomic absorption spectrometry (AAS) equipment (Perkin Elmer Analyst 460). The growth of A. spinosus contributed to an enhanced loss of the heavy metals from the soils. The loss of the heavy metals due to the growth of A. spinosus was more in soils from the refuse dumpsite than in the soils from the mechanic workshop. The rate of heavy metal loss was faster in the soil from mechanic workshop mechanic workshop than in the soil from the dumpsite. The trend of the rate of heavy metals loss was Cu>Zn>Pb>Cd for vegetated soil and Zn>Cu>Pb>Cd for non-vegetated soil. The rate of the heavy metal loss shows it will take lesser time to achieve 100% loss of the heavy metals in the vegetated soil than in the non-vegetated soils. There was no statistical difference between the loss of the heavy metals from the soils of the mechanic workshop and refuse dumpsite (p > 0.05). The results of this study indicated that A. spinosus with BCF values greater than 1 for Zn and Cu suggest that the plant uses hyperaccumaulation as the mechanism of remediation of the metals. The percentage loss of the heavy metals from the soils had a negative correlation with the amounts of heavy metals accumulated in the tissues of the plant, the rate of loss, and the bioconcentration factors. The ability of A. spinosus to be considered for phytoremediation has to be viewed with caution, as the translocation factor index indicates that all the metals investigated in this study were being translocated to the aerial parts of the plant.